How Thermodynamics Illuminates Population Interactions in Microbial Communities - Seto, Mayumi; Iwasa, Yoh (Frontiers in Ecology and Evolution, 2020)
In traditional population models of microbial ecology, there are two central players: producers and consumers (including decomposers that depend on organic carbon). Producers support surface ecosystems by generating adenosine triphosphate (ATP) from sunlight, part of which is used to build new biomass from carbon dioxide. In contrast, the productivity of subsurface ecosystems with a limited supply of sunlight must rely on bacteria and archaea that are able generate ATP solely from chemical or electric energy to fix inorganic carbon. These ‘light-independent producers’ are frequently not included in traditional food webs, even though they are ubiquitous in nature and interact with one another through the utilization of the by-products of others. In this review, we introduce theoretical approaches based on population dynamics that incorporate thermodynamics to highlight characteristic interactions in the microbial community of subsurface ecosystems, which may link community structures and ecosystem expansion under conditions of a limited supply of sunlight. In comparison with light-dependent producers, which compete with one another for light, the use of Gibbs free energy (chemical energy) can lead cooperative interactions among light-independent producers through the effects of the relative quantities of products and reactants on the available chemical energy, which is termed abundant resource premium. The development of a population theory that incorporates thermodynamics offers fundamental ecological insights into subsurface microbial ecosystems, which may be applied to fields of study such as environmental science/engineering, astrobiology, or the microbial ecosystems of the early earth.